Composições ocupacionais e características dos trabalhadores em atividades com impacto sobre o clima - Marcos Damasceno (2023)
Among the many changes that characterize the contemporary economy, global warming attracts attention as a phenomenon whose impact on production processes and on demand for work is likely to be significant. The technical requirements and innovations of “low carbon economy” not only can affect the skills required from workers but also occur together with other dynamics with potential impact on the composition and size of the workforce, like the population ageing process. Facing the fear of unavailability of workers qualified enough to occupy the many positions necessary for climate change adaptation, researchers have spread concepts and methods to discuss climate change impacts on the occupational structure, willing to advise public and private agents to speed up this economic transition and avoid that it enhances inequalities in the labor market. Following these steps and exploring aspects still unclear concerning the definition of the so-called “green” activities and occupations, this research investigated the occupational composition of economic activities that showed variations in greenhouse gases emissions employing a yet unused pairing of data from PNAD Contínua and from SEEG, a national greenhouse gases inventory developed by Observatório do Clima. Through a descriptive and trial analysis for the years of 2012 and 2019, occupational compositions were compared for the whole Brazilian country and activities that, judging by the volume of gases emissions, employed techniques with different pollution levels, as well as the characteristics of the workers themselves, such as age, gender, education, informality, and income. Besides shedding light on methodological challenges still unsolved, results suggest a possible association between the amount of gases emissions and occupational patterns distinguished by some of these characteristics, reinforcing the utility of SEEG as a data source for researches on this theme and the importance of extending the investigation to a wider range of economic activities and time intervals.